Navigating the Pacific: Solomon Islands Attempt to Gain Influence in the Middle of China-US Rivalry - Budi Wibawa, Priagung Arif; Heatubun, Rivelda P.; Widnyana, I Gede Wahyu; Mahendra, Yusril Ihza (Institute of International Studies, 2024)
The Pacific Islands Region is in the spotlight due to rising tensions between China and the U.S. This situation has escalated with China offering security pacts to Pacific Islands states in 2022. Despite most Pacific states rejecting the offer, the Solomon Islands, as the only country to accept it, caused concern for the U.S. and its allies. Considering that the Solomon Islands lack the traditional power to support their decision to align with China against the U.S. and its allies, it is an intriguing issue to delve into. This research aims to analyze the phenomenon by using qualitative-descriptive methods and the concept of Small States. This will give us a new way to understand how small states in the Pacific Ocean maneuver amidst the US-China rivalry by analyzing strategic indicators they can utilize rather than solely focusing on domestic circumstances to comprehend their decisions. We found that the Solomon Islands' ability to take such a risk stems from two sources of power: particular-intrinsic and derivative power. Intrinsically, the Solomon Islands hold geopolitical importance, being strategically crucial for both China's Belt and Road initiative and the U.S.'s attempt to retain its regional influence. Derivatively, the Solomon Islands' sole position to accept the security pact is highly valued by China. This will lead to a mutually beneficial relationship among them, and the Solomon Islands can benefit in security and economic terms. This research sheds light on how a small state navigates its interest in the epicenter of rivalry between two great powers.Keywords: China-US rivalry; Pacific Islands Region; small states; Solomon Islands